Unwavering Loyalty as the Portrayal of Devotion in Robert Eggers’ Nosferatu (2024) - Oktavia, Dian; Wijaya, Kusuma; Pasopati, Rommel Utungga (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study examines how loyalty represents devotion as displayed by the characters in Robert Eggers' film Nosferatu (2024). The research background is based on the understanding that devotion is a form of emotional commitment and deep values ​​that motivate individuals to maintain loyalty, even when faced with threats or moral conflict. The main focus of this study is to analyze how the actions, dialogue, and decisions of the main characters demonstrate loyalty as a manifestation of devotion rooted in the characters' psychology. This study uses a qualitative descriptive approach through film analysis. Data were collected using a note-taking method, namely watching the film Nosferatu (2024), noting scenes and dialogues relevant to the themes of loyalty and devotion, and identifying the conflicts and psychological motivations that arise in the characters. The analysis was carried out by interpreting the characters' actions based on the emotional context and the values ​​they consider important. The results of the analysis show that the characters in the film maintain loyalty to their loved ones or the values ​​they uphold, despite having to face inner dilemmas and threatening situations. This finding confirms that loyalty in this film functions as a reflection of complex devotion, influenced by feelings of love, moral responsibility, and values ​​considered irreplaceable.